Efek antigenotoksik ekstrak etanolik daun sirsak (Annona muricata Linn) terhadap frekuensi mikronukleus mukosa bukal tikus Sprague Dawley - Tyas Prihatiningsih; Tetiana Haniastuti; Dewi Agustina (Faculty of Dentistry, Universitas Gadjah Mada, 2017)
The effect of soursop leaves (Annona uricata linn) ethanolic extract on micronucleus frequency of buccal mucosa epithelium of Sprague dawley rats. Polycyclic aromatic hydrocarbons is one of the largest groups of carcinogen in environment. 7,12-Dimetillbez (α) antransena is a compound of PAH class that has genotoxic carcinogen potency. One of the most frequently applied genotoxicity tests is micronucleus test. Soursop is a plant that can grow well in Indonesia. Its leaves contain avonoid and acetogenin assumed to have potential chemopreventive and anticancer activities. The aim of this study was to assess the antigenotoxic effect soursop leaves ethanolic extraction the micronucleus frequency of DMBA-induced buccal mucosa of rat. This research was conducted on 24 male Sprague Dawley rats aged 5 weeks and divided into six groups. Carcinogenesis on the lingual dorsum of group I-III were induced by DMBA topically 3 times a week for 16 weeks, group II and III were not only induced by carcinogenesis, but also were given soursop leaves ethanolic extract of 100 and 200 mg/kg body weight for 18 weeks, group IV was given soursop leaves ethanolic extract 200 mg/kg body weight, group V was given DMSO 1% and group VI was given no treatment. After 18th week, buccal mucosa swab for micronucleus test was conducted and stained with Feulgen-Rossenbeck method. The number of micronucleus is calculated under a light microscope, data were analized using using one-way ANOVA followed by Tukey HSD. The result showed that the average of buccal micronucleus frequency of group II (13 ± 0.82) and group III (12 ± 0.96) were decrease signicantly (p<0,05) than group I (24 ± 1.71). From the experiment, it is concluded that the soursop leaves ethanolic extract has antigenotoxic effect shown by decreasing of the buccal micronucleus frequency of rat.ABSTRAKPolycyclic aromatic hydrocarbon atau PAH merupakan salah satu kelompok karsinogen terbesar di lingkungan. 7,12-Dimetillbez(α)antransena merupakan senyawa golongan PAH yang bersifat karsinogen genotoksik. Salah satu uji genotoksisitas yang paling sering dilakukan adalah uji mikronukleus. Sirsak merupakan tanaman yang tumbuh baik di Indonesia. Daun sirsak mengandung avonoid dan acetogenin yang diduga mempunyai potensi kemopreventif dan aktivitas antikanker. Tujuan penelitian ini adalah mengkaji efek antigenotoksik ekstrak etanolik daun sirsak terhadap frekuensi mikronukleus mukosa bukal tikus galur Sprague Dawley yang diinduksi dengan DMBA. Penelitian ini dilakukan pada 24 tikus Sprague Dawley jantan berumur 5 minggu yang dibagi secara acak dalam 6 kelompok. Karsinogenesis dorsum lidah tikus kelompok I – III diinduksi dengan DMBA secara topikal 3 kali dalam seminggu selama 16 minggu, kelompok II dan III selain diinduksi karsinogenesis, juga diberi ekstrak etanolik daun sirsak 100 dan 200 mg/kg BB setiap hari selama 18 minggu dan kelompok IV diberi ekstrak etanolik daun sirsak 200 mg/kg BB, kelompok V diberi DMSO 1% dan kelompok VI tidak diberi perlakuan. Setelah minggu ke-18, swab mukosa bukal dilakukan untuk uji mikronukleus kemudian sampel dicat dengan metode Feulgen-Rossenbeck. Jumlah mikronukleus dihitung di bawah mikroskop cahaya per 500 sel epitel mukosa bukal, lalu data dianalisis menggunakan one way ANOVA diikuti Tukey HSD. Hasil penelitian menunjukkan bahwa rerata frekuensi mikronukleus kelompok II (13 ± 0,82) dan kelompok III (12 ± 0,96) mengalami penurunan secara signikan (p<0,05) dibanding kelompok I (24 ± 1,71). Disimpulkan bahwa ekstrak etanolik daun sirsak mempunyai efek antigenotoksik yang ditunjukkan dengan penurunan frekuensi mikronukleus sel epitel mukosa bukal tikus.